Protective action of ppGpp in microcin J25-sensitive strains - Pomares, Maria Fernanda (2008)
As Escherichia coli strains enter the stationary phase of growth they become more resistant to the peptide antibiotic microcin J25. It is known that starvation for nutrients such as amino acids or glucose leads to increases in guanosine 3′,5′-bispyrophosphate (ppGpp) levels and that the intracellular concentration of this nucleotide increases as cells enter the stationary phase of growth. Therefore, we examined the effects of artificially manipulating the ppGpp levels on sensitivity to microcin J25. A direct correlation was found betweem ppGpp accumulation and microcin resistance. Our results indicate that the nucleotide is required to induce production of YojI, a chromosomally encoded efflux pump which, in turn, expels microcin from cells. This would maintain the intracellular level of the antibiotic below a toxic level.